Return Migration is Not the End: How Families, Markets, and Institutions Shape Reintegration in Punjab Province, Pakistan - Hussain, Zubair (Electronic Journal of Business and Management, 2026)
Return migration is often assumed to restore stability, yet reintegration can be a second rupture shaped by household pressures, market uncertainty, and social reception. Drawing on 30 semi-structured interviews with return migrants living in Punjab Province, Pakistan, this qualitative study examines how economic recovery, social belonging, and cultural adjustment interact to shape post-return outcomes. Using reflexive thematic analysis, the findings identify four reinforcing dynamics: limited conversion of overseas skills into decent work, rapid depletion of savings through restart costs, relational pressures driven by expectations and mistrust, and institutional inconsistencies that raise transaction costs and constrain opportunity. Family return intensifies these pressures by placing children’s schooling and caregiving responsibilities at the center of livelihood decision-making. The study argues that sustainable reintegration requires coordinated governance skills validation, accessible working-capital support, reliable service navigation, trust-building market mechanisms, and family-focused transition support rather than isolated employment or loan interventions.